KAJIAN POLA SEBARAN SEDIMEN PADA SALURAN BANJIR SUNGAI KRUENG ACEH - Alfaisal Alfaisal; Syamsidik Syamsidik; Masimin Masimin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: Krueng Aceh River is one of the main river in Aceh Province located in Krueng Aceh River Basin Area (DAS) with in 17.800 Acre wide and 145 km length. In order to minimize the flood impact in Banda Aceh with 1.300 m3/s flood discharge design, 900 m3/s discharge has been redirected to Krueng Aceh river floodway while the rest had distributed to the Krueng Aceh existing river. Meanwhile for 900 m3/s of the flood discharge is distributed through the floodway from the diversion weir. It is worried that the water will reach the top of the dike in some location of the main river. It is because of the swallow in the estuary due to the sediment concentration. This research aims is to investigate the sediment distribution pattern, estimating volume of the deposited sediment. Furthermore, the investigation is also to find how the sediment transport occured while the flood. The flood simulation had been done by the Delft3D Model which combine with the hydrodynamics and the sediment transport calculation. This model use 20x20 m grid for the domain. Topography and bathimetry data were collected from Balai Wilayah Sungai Sumatera–I (BWSS-I). Sediment characteristic had been primerly collected in the field. Simulation results had shown that the sediment distribution pattern on Krueng Aceh river floodway has a particular pattern remain relatively on the right side of the estuary. The sediment increase of 868.236 m3 and produced 2.039.560 m3 massive erosion during 3 month simulation with flood scenario. The sedimentation process is smaller compared to the erosion. But the erosion only happen in the area with the greater than value of current. The simulation complimented by 5 years return flood design was uncapable to flush the sediment which deposited on the eastern side of the estuary. The phenomenon happened because of the river morphology with it meandering channel, not enough length of left jetty and the current that not equally distributed. The solution for this problem is by lengthening the left side of the jetty toward the breakwater and constructing the river training toward the current in the left side of the estuary. Abstrak: Krueng Aceh merupakan salah satu sungai besar di Provinsi Aceh, berada dalam wilayah Daerah Aliran Sungai (DAS) Krueng Aceh dengan luas DAS 17.800 Ha dan panjang sungai 145 Km. Untuk meminimalisir terjadinya banjir di kota Banda Aceh dengan debit banjir rancangan sebesar 1.300 m3/detik, maka untuk debit banjir 400 m3/detik dialirkan melalui Sungai Kr. Aceh existing. Sedangkan untuk debit banjir sebesar 900 m3/detik dialirkan melalui saluran banjir dari bendung pelimpah banjir (Diversion Weir). Pada beberapa lokasi di sungai induk dikhawatirkan elevasi muka air akan mencapai puncak tanggul. Ini akibat dari pendangkalan yang terjadi di bagian muara dengan adanya konsentrasi sedimen. Penelitian ini bertujuan untuk mengetahui pola sebaran sedimen pada bagian hilir saluran banjir, mengetahui volume sedimen yang terkonsentrasi setelah kejadian banjir dan mengetahui bagaimana pergerakan sedimen terjadi setelah banjir. Penelitian dilakukan dengan simulasi numerik menggunakan software Delft3D yang berfungsi sebagai model traspor sedimen pada lokasi simulasi. Model ini menggunakan grid dengan ukuran 20 m x 20 m. Data yang digunakan adalah data topografi dan batimetri dari Balai Wilayah Sungai Sumatera-I dan parameter sedimen dari hasil pengambilan sampel di lokasi kajian. Hasil simulasi menunjukkan bahwa, pola sebaran sedimen pada saluran banjir sungai Krueng Aceh memiliki pola yang relatif tetap khususnya pada sisi kanan muara, peningkatan sedimen setelah terjadinya banjir sebesar 868.236 M3 dan yang tergerus sebesar 2.039.560 M3. Artinya volume sedimen yang mengendap lebih kecil dari pada yang tergerus. Namun yang tergerus tersebut hanya pada jalur dengan arus yang lebih besar. Hasil dari simulasi dengan menggunakan debit banjir rancangan lima tahunan, sedimen yang berada di sisi kanan muara tidak mampu tergelontor ke laut. Hal ini diakibatkan karena bentuk meander saluran yang berbelok, jetty di sisi kiri yang kurang panjang dan arus banjir yang tidak merata. Upaya yang dapat dilakukan yaitu dengan memperpanjang jetty sisi kiri sampai kedalaman gelombang pecah dan membuat river training untuk mengarahkan arus ke bagian sedimen di sisi kanan muara.